A Wisdom for Anglican Life: Lambeth 1998 to Lambeth 2008 and Beyond - Ford, David (Journal of Anglican studies, 2006)
This keynote paper was delivered at the Society for the Study of Anglicanism which gathered at the AAR Annual Meeting in Philadelphia in November 2005. On the basis of many years of observation and participation in the life of the Anglican Communion, I attempt to offer in this article a ‘Wisdom for Anglican Life’ — a wisdom which takes seriously the unity and koinonia of the Church as rooted in the cross of Jesus Christ and the love of God. Such wisdom is rooted in the faithful worship of the Church but also engages seriously with the struggles of the world. It counsels gentleness, kindness, forgiveness and above all patience in matters of dispute, and embraces the thoughtful but rigorous communal study of Scripture. This article ultimately suggests that a pressing task facing the Communion today is to learn afresh how to be Anglican Christians in the twenty-first century.